A cross-sectional study of extent and causes of interruption of treatment of tuberculosis in a tuberculosis unit of Purba Bardhaman district of West Bengal, India - Chinmay Nandi,; Kaushik Mitra,; Dipankar Bhaumik, (Asian Journal of Medical Sciences, 2023)
Background: Tuberculosis (TB) is a communicable disease which requires prolonged treatment and having both medical and social dimensions. Adherence to treatment is very important issue in successful treatment of TB. Directly observed therapy was a key strategy in The Revised National TB Control Program. However, treatment interruption is very common. Aims and Objectives: The objective of this study is to assess the nature, extent, and reasons for interruption of treatment in Bhatar TB Unit (TU) of Purba Bardhaman district of West Bengal. Materials and Methods: The study was a descriptive and cross-sectional study with two components. The study was conducted in the area covered under Bhatar TU of Burdwan district of West Bengal. Complete enumeration technique was followed in the study. In the first component of the study, 231 study subjects were found by complete enumeration, out of which 26 were discarded due to incomplete records. In the other component, 90 study subjects were interviewed at the beginning of treatment and after treatment interruption, if any. Data were analyzed using RStudio. Results: Out of the group with only record review, 205 subjects were included in the study, out of which 160 (78.05%) were male and 45 (21.95%) were female. In the other group with both record review and interview, out of 90 subjects, 64 (71.1%) were male and 26 (28.9%) were female. Out of 295 cases, 270 (91.5%) were new and 25 (8.5%) were previously treated. Out of 295 subjects, 36 (12.2%) had interrupted treatment. Seven persons out of 36 had interrupted more than once. Thirty-four persons had interrupted in intensive phase of treatment. Thirty-two persons had taken 10–20 days before interruption of treatment. The most common reason for interruption of treatment was “Not willing to take tablets.” Among the other reasons were “Side effects,” “Hospitalization,” “Away from home,” etc. Conclusion: Non-compliance to anti-tubercular drugs remains an important issue in the elimination of TB.